2006
DOI: 10.1002/ppap.200600005
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Bacteria by the Plasma Pencil

Abstract: Summary: A device capable of generating a relatively long cold plasma plume has recently been developed. The advantages of this device are: plasma controllability and stability, room temperature and atmospheric pressure operation, and low power consumption. These features are what is required from a plasma source to be used reliably in material processing applications, including the biomedical applications. In this communication we describe the device and we present evidence that it can be used successfully to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(135 citation statements)
references
References 14 publications
2
123
0
8
Order By: Relevance
“…As predicted by prior literature on plasma-based sterilization, the introduction of a small amount of oxygen in the helium flow actually increased the efficacy of the plasma inactivation [45,47].…”
Section: Bacteria Decontaminationsupporting
confidence: 59%
See 1 more Smart Citation
“…As predicted by prior literature on plasma-based sterilization, the introduction of a small amount of oxygen in the helium flow actually increased the efficacy of the plasma inactivation [45,47].…”
Section: Bacteria Decontaminationsupporting
confidence: 59%
“…Atmospheric pressure plasma jet is one of the most efficient sources for decontamination [45][46][47][48].…”
Section: Bacteria Decontaminationmentioning
confidence: 99%
“…Further examinations were done by cooling the RF electrode with water to decouple the temperature effect and the effect of the discharge itself. This results in a significant increase of about 2 log 10 decontamination for temperatures lower than 100 • C. Laroussi et al (2006) present a plasma pencil designed as shown in figure 9a. The dielectric tube has a 2.5 cm diameter and is 12 cm long, the 2 copper electrodes are separated by a 0.5 − 1 cm gap.…”
Section: Atmospheric Pressure Plasma Jetmentioning
confidence: 99%
“…One of the most widely used APP applicators is the tube design which includes: the plasma jet [4,5], plasma needle [6], plasma pencil [7], and microplasma jet [8]. The plasma operational modes of these tube sources are influenced by their electrode configuration, gas flow rate, gas type, applied power and the distance between the plasma applicator nozzle and treated surface [9][10][11].…”
Section: Introductionmentioning
confidence: 99%